Frontline therapy of acute promyelocytic leukemia: Randomized comparison of ATRA and intensified chemotherapy versus ATRA and anthracyclines - Lengfelder, Eva; Nowak, Daniel; Hecht, Anna; Hofmann, Wolf-Karsten (European journal of haematology, 2018)
Objectives Randomized comparison of two treatment strategies in frontline therapy of acute promyelocytic leukemia (APL): all-trans retinoic acid (ATRA) and double induction intensified by high-dose cytosine arabinoside (HD ara-C) (German AMLCG) and therapy with ATRA and anthracyclines (Spanish PETHEMA, LPA99). Patients and results Eighty of 87 adult patients with genetically confirmed APL of all risk groups were eligible. The outcome of both arms was similar: AMLCG vs PETHEMA: hematological complete remission 87% vs 83%, early death 13% vs 17% (P = .76), overall survival, event-free survival, leukemia-free survival, cumulative incidence of relapse at 6 years 75% vs 78% (P = .92); 75% vs 68% (P = .29); 86% vs 81% (P = .28); and 0% vs 12% (P = .04, no relapse vs four relapses), respectively. The median time to achieve molecular remission (RT-PCR negativity of PML-RARA) was 60 days in both arms (P = .12). The AMLCG regimen was associated with a longer duration of neutropenia (P = .02) and a higher rate of WHO grade ≥3 infections. Conclusions The small number of patients limits the reliability of conclusions. With these restrictions, the outcomes of both approaches were similar and show the limitations of ATRA and chemotherapy. The HD ara-C-containing regimen was associated with a lower relapse rate in high-risk APL.
Gesehen am 04.05.2020
First published: 07 November 2017